Are the Myokines the Mediators of Physical Activity-Induced Health Benefits? - Di Raimondo, Domenico; Tuttolomondo, Antonino; Musiari, Gaia; Schimmenti, Caterina; D128;™Angelo, Alessandra; Pinto, Antonio (Current Pharmaceutical Design, 2016)
Background: The concept of the muscle as a secretory organ, developed during the last decades, partially answers to the issue of how the crosstalk between skeletal muscle and distant tissues happens. The beneficial effects of exercise transcend the simple improved skeletal muscle functionality: systemic responses to exercise have been observed in distal organs like heart, kidney, brain and liver. Increasing data have accumulated regarding the synthesis, the kinetics of release and the biological roles of muscular cytokines, now called myokines. The most recent techniques have meaningfully improved the identification of the muscle cell secretome, but several issues regarding the extent of secretion from the muscle as well as the actions of the myokines remain unexplained. Methods: The goal of this review is to provide an update about the secretory properties of skeletal muscle during and after an acute bout of exercise and after exercise training, showing the main experimental evidences, but also speculate about the possible therapeutic use of the physical training-induced circulating factors, especially in some categories of patients in which the baseline conditions are heavily damaged by one or more pathological conditions. Results: studies on myokines are relatively recent, and to date most of the evidence available in humans has focused on the biological role of Il-6 during muscle contraction. Regarding to the myokines more recently identified, for example myostatin, fibroblast growth factor 21 (FGF21), secreted protein acidic and rich in cysteine (SPARC) or follistatin-like 1 some of these seem to be promising therapeutic agents, but our awareness about their potential benefits towards human health is only at the beginning. Conclusion: for many of the myokines identified to date, the information available is limited and not enough to characterize precise functions and activities carried out by those in man. Several issues need to be addressed by future studies, tailored to ascertain accurately and surely the biological role and the therapeutic potential of some myokines.
Keywords: Myokines